CHARACTERISTICS OF THE DEVELOPMENT OF RETAIL TRADE SERVICES UNDER THE CONDITIONS OF SOCIAL-ECONOMIC CHANGES (Marketing Journal, 2025)
The article considers general issues of formation and development of theoretical and methodological aspects of assessment of the trade services development system in the context of socio -economic transformations. In the course of the presentation of the work, the main elements of assessment of the trade services development system are summarized and structured, its functions are systematized, the factors of its development are studied, as well as the role of assessment of the trade services development syst em in the formation of a platform for sustainable trade development and the national economies that form it.
Keywords: economy; trade trade services; system evaluation; trade enterprises; commercial activity; efficiency; trade system; technological system; efficiency indicators. № 1 516